Cochrane's risk of bias tool in the context of psychotherapy outcome research. (4th May 2018) - Munder, Thomas; Barth, Jürgen
Abstract: The Cochrane risk of bias tool (RoB) is a widely used measure for methodological quality of randomized controlled trials. This paper discusses RoB's rationale and risk of bias domains, reports on its application in current psychotherapy meta-analyses, and offers comments regarding the application of RoB in the context of psychotherapy outcome research. Our suggestions include focusing on patient's and therapist's expectations when judging the domain "blinding of personnel and participants" and paying greater attention to the domain "selective outcome reporting" and to matters of "treatment implementation." Clinical or methodological significance of this article: This paper discusses the rationale of a widely used tool to assess the methodological quality of primary studies for meta-analysis and provides suggestions for its use in the context of psychotherapy outcome research.